To solve the equation, we need to simplify the left side and isolate the variable.
Starting with 5(9z + 2) - 5 = 185:
First, distribute 5 to both terms inside the parentheses.
45z + 10 - 5 = 185
Next, combine like terms.
45z + 5 = 185
Subtract 5 from both sides of the equation.
45z = 180
Divide both sides of the equation by 45.
z = 4
5(9z + 2) - 5 = 185
5 answers
thats wrong
My apologies for the mistake. Let's solve the equation correctly.
Starting with 5(9z + 2) - 5 = 185:
First, distribute 5 to both terms inside the parentheses:
45z + 10 - 5 = 185
Combine like terms:
45z + 5 = 185
Subtract 5 from both sides of the equation:
45z = 180
Divide both sides of the equation by 45:
z = 180/45
Simplifying the right side:
z = 4
So the solution to the equation is z = 4.
Starting with 5(9z + 2) - 5 = 185:
First, distribute 5 to both terms inside the parentheses:
45z + 10 - 5 = 185
Combine like terms:
45z + 5 = 185
Subtract 5 from both sides of the equation:
45z = 180
Divide both sides of the equation by 45:
z = 180/45
Simplifying the right side:
z = 4
So the solution to the equation is z = 4.
-16z - 19 = -12z + 9
To solve the equation, we need to simplify the expression and isolate the variable.
Starting with -16z - 19 = -12z + 9:
First, combine like terms:
-16z + 12z = 9 + 19
Simplifying:
-4z = 28
Next, divide both sides of the equation by -4 to isolate z:
-4z / -4 = 28 / -4
Simplifying further:
z = -7
Therefore, the solution to the equation is z = -7.
Starting with -16z - 19 = -12z + 9:
First, combine like terms:
-16z + 12z = 9 + 19
Simplifying:
-4z = 28
Next, divide both sides of the equation by -4 to isolate z:
-4z / -4 = 28 / -4
Simplifying further:
z = -7
Therefore, the solution to the equation is z = -7.